Characterizing pig value chains in Vietnam: descriptive analysis from survey data - Duong Nam Ha; Nguyen Thi Thu Huyen; Ninh Xuan Trung; Tran Van Long; Nguyen Anh Duc; Vu Khac Xuan; Nguyen Thi Duong Nga; Pham Van Hung; Rich, Karl M.; Unger, Fred; Lapar, Ma. Lucila (Vietnam National University of Agriculture, 2014)
The traditional pig sector plays a significant role in Vietnam’s economy from production, especially for farmers in rural areas, to consumption (more than 90% of pork consumed is supplied by conventional wet markets). At the same time, the traditional pig sector is under threat from animal health and food safety risks that impact both its profitability and future viability. However, little research exists on defining key intervention points that could manage risks in a propoor, cost-effective manner. Our study highlighted and reviewed the contrast between pig value chains in two provinces (Hung Yen and Nghe An) that represent different levels of economic development in the county. Based on semi-structured questionnaires, 400 pig producing farmers and 400 pork consumers were surveyed in both provinces during July and August 2013, paying particular attention to typologies of production and consumption in rural, semi-urban, and urban zones. We also obtained information on 200 other intermediary value chain actors through semi-structured and in-depth interviews. Preliminary descriptive analysis revealed the main characteristics of various actors in the sampled value chains, including (vet and feed) input suppliers, producers, traders, slaughterhouses (or abattoirs), processors, retailers, and consumers. In particular, we found that actors in Hung Yen are more likely to be active and commercialised in pig value chains than those in Nghe An. At the same time, Nghe An is exposed to operate its chains more ‘self-sufficiently’, with ownproduced inputs, particularly feeds, and has more state-owned farms involved in breed supply. In both study sites, middlemen often perform multiple functions and are generally the most powerful actors in the surveyed chains since they have better access to information and dominate value-added activities. This may imply a potential control point for risk management in response to diseases transmitted in short-term as well as (pro-poor) profit distribution in longerterm. Moreover, the behaviours of actors in these two provinces are dissimilar in terms of production and consumption practices as a result of differences in production scale, knowledge, attitude and habits. Information from this study will provide more insightful understanding of these existing value chains and serve as the base for further economic and risk analysis.